Continuous inline monitoring of glucose in an organ-on-chip using FreeStyle™ libre glucometers - Sánchez-Salazar, Mónica Gabriela; Garza-Garza, Regina; Crespo-López Oliver, Regina; Jerezano-Flores, Valeri Sofía; Gallegos-Martínez, Salvador; Ramos-Meizoso, Sofía; Verduzco-Valenzuela, Manuel; Trujillo-de Santiago, Grissel; Alvarez, Mario Moisés (Frontiers in Lab on a Chip Technologies, 2024)
Organ-on-chips have become an effective platform for studying the physiology of tissues and organs and for evaluating the safety and efficacy of drugs. In these systems, the inline monitoring of key parameters of biological performance (i.e., glucose, oxygen, or lactic acid concentrations) provides valuable information regarding the cell/tissue physiological state. However, significant limitations still exist when attempting to obtain inline information in these systems, and the microsensing technology of on-chip measurement of key parameters is still limited by size, cost, and availability. Here, we demonstrate the use of a commercially available glucometer (FreestleTM Libre; Abbott), normally used for continuous determination of blood glucose levels, to provide continuous inline measurements of the glucose concentration in tumor-on-chips. Here, we employed a colorectal tumor-on-chip as a first demonstration model and measured the on-chip concentration of glucose continuously for extended culture times (2 weeks). We show that inline glucose readings are reproducible and enable the accurate determination of glucose consumption rates (GCRs) by a tumor cell culture. In turn, the GCR measurements provide valuable information regarding the changes in the metabolic activity of the on-chip cultures following inlet perturbations (i.e., delivery of pulses of glucose, culture media additives, and drugs). Inline continuous glucose sensors will be useful tools in organ-on-chip research and will greatly enable cancer research in tumor-on-chip systems.Results and DiscussionHere, we demonstrate the use of a commercial glucose sensor (Freestyle®) to conduct continuous inline determinations of the glucose concentration in organs-on-chip in a continuous manner.